2013
DOI: 10.1021/ci400060j
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Drug Resistance Mechanism against HCV NS3/4A Protease Inhibitors Vaniprevir and MK-5172 by the Combination Use of Molecular Dynamics Simulation, Residue Interaction Network, and Substrate Envelope Analysis

Abstract: Hepatitis C virus (HCV) NS3/4A protease is an important and attractive target for anti-HCV drug development and discovery. Vaniprevir (phase III clinical trials) and MK-5172 (phase II clinical trials) are two potent antiviral compounds that target NS3/4A protease. However, the emergence of resistance to these two inhibitors reduced the effectiveness of vaniprevir and MK-5172 against viral replication. Among the drug resistance mutations, three single-site mutations at residues Arg155, Ala156, and Asp168 in NS3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 78 publications
1
37
0
Order By: Relevance
“…In a recent study, Xue et al further investigated the structural basis of drug resistance mutations R155K, A156T, and D168A against MK-5172 and MK-7009. 25 …”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Xue et al further investigated the structural basis of drug resistance mutations R155K, A156T, and D168A against MK-5172 and MK-7009. 25 …”
Section: Introductionmentioning
confidence: 99%
“…At the present time, molecular modeling methods have been proved to be the effective techniques for investigating the drug resistance mechanism of inhibitors. Several typical works aimed at the drug resistance mechanism studies related to the HCV NS3/4A protease and NS5B polymerase have been reported in the past few years (Davis and Thorpe, 2013;Guo et al, 2006;Klibanov et al, 2012;Welsch et al, 2008Welsch et al, , 2012Xue et al, 2012Xue et al, , 2013Xue et al, , 2014Guan et al, 2014;Jiao et al, 2014;Yi et al, 2012;Wang et al, 2014).…”
mentioning
confidence: 99%
“…Some second generation DAA regimens include agents with activity against RAVs selected by first generation agents. For example, grazoprevir, a second generation PI potently inhibits the R155K mutant that is highly resistant to first generation agents in this class [80]. However, this issue is more challenging with NS5A inhibitors, which are included in most approved regimens and in all regimens in latestage development.…”
Section: Key Pointmentioning
confidence: 99%